STRATEGI AMERIKA SERIKAT MENGGANDENG NEGARA KAWASAN ASIA PASIFIK BEGABUNG KE INDO PACIFIC ECONOMIC FRAMEWORK (IPEF) - Tarigan, Sri Wahyuni; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzed the Indo-Pacific Strategy of U.S to encourage Asia Pacific countries to join Indo-Pacific Economic Framework (IPEF) partnership. IPEF is an economic framework initiated by Joe Biden’s administration that seeks to advance discussion about crucial economic issues such as trade, supply chain, clean economy and fair economy. This research used a neorealism perspective to explain that countries tend to compete for power in anarchic international system where there is no highest authority that regulates the behaviors of countries in international relations. Theory used in this research is institutional balancing in which countries take advantages of the domination of multilateral institutions to give pressure and threaten other countries so as to create security. The method used in this research is qualitative method with document analysis technique which was cited from books, journal article, or websites and other references that are relevant. The result of this research is that the U.S applied loose rules for countries who had wanted to join IPEF membership. Those Loose rules mean that all members have freedom to choose their commitment under one or more pillars of IPEF that align with their national interests without any requirement to be bound and participate in all cooperation under those four existing pillars. Keywords: U.S, IPEF, Indo-Pacific Policy, Tiongkok